Identification of essential genes in Caenorhabditis elegans through whole-genome sequencing of legacy mutant collections. Issue 12 (22nd September 2021) - Li-Leger, Erica; Feichtinger, Richard; Flibotte, Stephane; Holzkamp, Heinke; Schnabel, Ralf; Moerman, Donald G
Abstract: It has been estimated that 15%–30% of the ∼20, 000 genes in C. elegans are essential, yet many of these genes remain to be identified or characterized. With the goal of identifying unknown essential genes, we performed whole-genome sequencing on complementation pairs from legacy collections of maternal-effect lethal and sterile mutants. This approach uncovered maternal genes required for embryonic development and genes with apparent sperm-specific functions. In total, 58 putative essential genes were identified on chromosomes III–V, of which 52 genes are represented by novel alleles in this collection. Of these 52 genes, 19 (40 alleles) were selected for further functional characterization. The terminal phenotypes of embryos were examined, revealing defects in cell division, morphogenesis, and osmotic integrity of the eggshell. Mating assays with wild-type males revealed previously unknown male-expressed genes required for fertilization and embryonic development. The result of this study is a catalog of mutant alleles in essential genes that will serve as a resource to guide further study toward a more complete understanding of this important model organism. As many genes and developmental pathways in C. elegans are conserved and essential genes are often linked to human disease, uncovering the function of these genes may also provide insight to further our understanding of human biology. Abstract : Estimates suggest that 15-30% of C. elegans genes are essential, yet many of these remain to be identified or characterized. The authors performed whole-genome sequencing on legacy collections of maternal-effect lethal and sterile mutants, uncovering novel alleles representing 52 essential genes. 19 genes were selected for further functional characterization, revealing defects in embryogenesis and fertilization. The resulting catalogue of mutant alleles in essential genes is a resource to guide further study toward a more complete understanding of this important model organism.